Agricultural law and sustainable rural development - Velazco Mugarra, Miriam (Przegląd Prawa Rolnego, 2023)
Agricultural law seen in the context of rural development should respond to current challenges. Prioritising the organisation of a system that integrates multiple functions and dimensions of agricultural policy and sustainable rural development has become a social necessity. It is proposed therefore that the law on sustainable rural development adopted in Spain be a reference point for the legislative work in Cuba ensuring that agricultural law relates to the environmental aspects of agriculture, food and rural development. In this way the basic tenets of rural development can be preserved, the stability of farms ensured and the quality of life in these areas improved.